Teacher collaboration in a public school to set up language resource centers: portraying advantages, benefits, and challenges (2008)
In the present article, the author attempts to describe the benefits, challenges, advantages and disadvantages experienced by teachers in a public school when working collaboratively to implement a language resource center in their institution. Taking as a point of departure the development of a proposal to implement the resource center in their school, some teachers engaged in group work in order to attain the different objectives that were stated at the beginning of the process, thus encountering a number of difficulties and challenges. When overcome, these difficulties and challenges rendered good opportunities for teachers to develop further in their professional and personal life as well as to improve the school environment and classroom practice. Key words: Collaborative work, language resource center, teacher professional development En el presente artículo, el autor se propone describir los beneficios, desafíos, ventajas y desventajas que un grupo de profesores de un colegio público encontraron al trabajar colaborativamente para implementar un centro de recursos de idiomas. Tomando como punto de partida la construcción de su propuesta de implementación del centro de recursos para la institución, algunos profesores decidieron trabajar en grupo para alcanzar los objetivos planteados al comienzo del proceso, encontrando una serie de dificultades y desafíos. Al superar dichas dificultades y desafíos, los docentes hallaron oportunidades para su desarrollo profesional y personal así como para el mejoramiento del ambiente escolar y del ejercicio docente. Palabras clave: Trabajo colaborativo, centro de recursos de lenguas, desarrollo profesional docente